UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN NANGKA (Atrocarpus heterophyllus Lam) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Aulia Debby Pelu; Hamka Sangkala; Akbar Mahfudz Ismail (Jurnal Sains dan Kesehatan, 2022)
Jackfruit leaves are one of the medical plants that have many benefits. In general, jackfruit leaves are known as animal feed, but behind their function as animal feed, jackfruit leaves have health benefits because jackfruit leaves contain antimicrobials including flavonoids, tannins, saponins that can dissolve in water and can work to damage cytoplasmic membranes and denature cell proteins bacteria. Staphylococcus aureus is a gram-positive bacterium and is arranged in clusters (like grapes). Some infectious diseases caused by these bacteria are impetigo, boils, acne, wound infections, toxic shock syndrome, and other types of pathogenic. This study was conducted to determine the effect of jackfruit leaf extract dissolved using 70% ethanol as a solvent on the growth of staphylococcus aureus bacteria. The method used is the maceration method for the phytochemical screening test, and the disc diffusion method for the antibacterial activity test. The results of the phytochemical screening contained secondary metabolite compounds in jackfruit leaves and for the results of the antibacterial activity test of jackfruit leaf ethanol extract against the growth of staphylococcus aureus bacteria there was antibacterial activity inhibition with high inhibition at 80% concentration with a diameter of 13mm.